Comparing Solar Energy Investment Policies: Legal Perspectives from Indonesia and Vietnam - Sudirman, Lu; Nurlaily, Nurlaily; Jaya, Febri (Universitas Islam Negeri Raden Fatah Palembang, 2025)
Although Indonesia possesses significant potential for solar energy, it remains behind Vietnam, highlighting the critical need for policy and investment reforms to meet the increasing demand for renewable energy. This study aims to explores the normative issues within the Indonesian legal framework for investment and benchmarks it against Vietnam’s to assess the legal gap that may have hindered Indonesia’s progress in supporting solar technology investments. This study adopts a normative-empirical approach by integrating normative legal analysis of regulatory frameworks with the presentation and examination of empirical data. The empirical dimension of this research incorporates analysis of implementation outcomes, including renewable energy capacity data, carbon footprint measurements, and regulatory effectiveness indicators. The results of this study highlights normative inadequacies from Indonesia, with the lack of foundational normative support, followed by the lack of support in the form of complimentary regulations. Vietnam, on the other hand, has a significantly more developed framework to support investments in solar technology, serving as comparative evidence of the stark contrast between the country’s success and Indonesia’s ongoing challenges.